Problematics of Consumer Protection in Business Activities - Asri, Cahya Purnama; Artha, Bhenu; Bahri, Bahri (Fakultas Hukum Universitas Widya Mataram, 2022)
Abstract The problem that occurs in consumer protection is the lack of regulation regarding setting minimum and maximum standards in the value issued by each product and brand so that consumers feel confused in determining these products and weak supervision can affect producers and business actors in setting value so that it has the potential to harm consumers. components that affect consumer protection are caused by the application of regulations or consumer protection rules that are not comprehensive, and leave gaps that can harm consumer rights in the cellular ecosystem, especially if it involves non-financial institutions, and consumer protection by non-financial institutions is much weaker than protection by bank payment service Keywords: Consumer Protection, Consumer Law, Problems